Exosomal Long NonCoding Rnas as Cancer Biomarkers and Therapeutic Targets - O. A. Beylerli; I. F. Gareev; V. N. Pavlov; Zhao Shiguang; Chen Xin; V. V. Kudriashov (Креативная хирургия и онкология, 2020)
Extensive study of extracellular vesicles began about ten years ago. Exosomes are extracellular membrane vesicles 30–100 nm in diameter secreted by various types of cells and present in most biological fluids. For a long time they were considered non-functional cellular components. However, it has been proven that they serve as a means of intercellular exchange of information. They can move bioactive molecules such as proteins, lipids, RNA, and DNA. Several studies have shown that their contents, including proteins and non-coding nucleic acids, may be of particular interest as biomarkers of diseases. The most promising of all these molecules are non-coding RNAs (ncRNAs), including microRNAs and long non-coding RNAs (lncRNAs). LncRNAs are a large group of non-coding RNAs (ncRNAs) longer than 200 nucleotides. As regulatory factors lncRNAs play an important role in complex cellular processes, such as apoptosis, growth, differentiation, proliferation, etc. Despite many advances in diagnosis and treatment (surgery, radiation therapy, chemotherapy), cancer remains one of the most important public healthcare problems worldwide. Every day brings a better understanding of the role of exosomes in the development of cancer and metastases. Liquid biopsy has been developed as a method for the detection of cancer at an early stage. This is a series of minimally invasive tests of bodily fluids offering the advantage of real-time tracking of the tumour development. In fact, circulating exosomal lncRNAs have been found to be closely linked to processes of oncogenesis, metastasis and treatment. In this paper we review current studies into the functional role of exosomal lncRNAs in cancer and discuss their potential clinical use as diagnostic biomarkers and therapeutic targets for cancer.